Personality dimensions, depression, and eating behavior in individuals seeking bariatric surgery: a cluster analysis - Rodolico, Alessandro; La Rosa, Valentina Lucia; Romaniello, Caterina; Concerto, Carmen; Meo, Valeria; Saitta, Giulia; Sturiale, Serena; Signorelli, Maria Salvina; Wang, Ray; Solhkhah, Ramon; Phalen, Catherine; Kelson, Michael; et al. (Frontiers in Nutrition, 2024)
Psychiatric comorbidity is frequent in bariatric surgery candidates. This study aimed to classify bariatric surgery patients according to patterns of preoperative measures of the severity of the eating disorder (ED), depression, and personality traits. In the present cross-sectional study, 115 adult candidates for bariatric surgery (75 females, 65.22% of sample; mean age 37) were considered for analysis. Patients' sociodemographic and psychopathological variables were collected. K-Means clustering analysis was adopted to classify bariatric surgery candidates according to their preoperative Eating Disorder Inventory-2 (EDI-2) scores. In addition, we assessed depression and personality traits using the Beck Depression Inventory-2 (BDI-2) and the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). Cluster analysis based on EDI-2 revealed two preoperative patterns: higher severity (n=39), and low severity (n=76). The more severe EDI-2 group had higher scores on the BDI-2 and presented higher scores on several MMPI-2 dimensions, particularly those related to anxiety (Psychastehnia, Anxiety, Fears, Obsessiveness), depression (Depression, including both content and clinical MMPI-2 subscales), externalizing symptoms (Anger, Cynicism, Type A Behavior), and social functioning (Social Introversion, Family Problems, Work Interference). Eating disorders symptoms in candidates for bariatric surgery are closely related to depression and different psychological conditions assessed with MMPI-2. These psychological variables should be evaluated preoperatively and targeted with more specific psychological interventions.